Precious metal abundance and economic growth: Evidence from top precious metal producer countries - Bildirici, Melike E.; Gokmenoglu, Seyit M. (ELSEVIER SCI LTD, 2020)
In this study, metal curse hypothesis was suggested for top precious metal producer countries, i.e. Australia, Canada, Mexico, Philippines, Peru, South Africa and the USA by using nonlinear Smooth Transition Autoregressive Distributed Lag (STARDL) models for the period 1963-2017. We used precious metal production data as an indicator for resource richness. According to the analysis results of STARDL models, we found statistically significant regime specific long-run and short-run relationships between economic growth and each precious metal type under analysis. We couldn't find supporting results for metal curse for Canada, Philippines, Peru, South Africa and the USA, but the positive effect of each precious metal abundance is asymmetric between the regimes. For Australia and Mexico, the effect of precious metal abundance on economic growth is various depending on precious metal type, the regime which the economy is in, the short- and long-run.
Keywords: Economic growth; Precious metals; Metal curse; Resource curse; STARDL; NATURAL-RESOURCE ABUNDANCE; INSTITUTIONAL QUALITY; FINANCIAL DEVELOPMENT; DUTCH DISEASE; CURSE; OIL; PANEL; INEQUALITY; DEPENDENCE; EDUCATION; Environmental Sciences & Ecology